1997
DOI: 10.1091/mbc.8.9.1677
|View full text |Cite
|
Sign up to set email alerts
|

G alpha 3 regulates the cAMP signaling system in Dictyostelium.

Abstract: The Dictyostelium discoideum developmental program is initiated by starvation and its progress depends on G-protein-regulated transmembrane signaling. Disruption of the Dictyostelium G-protein a-subunit Ga3 (ga3-) blocks development unless the mutant is starved in the presence of artificial cAMP pulses. The function of Ga3 was investigated by examining the expression of several components of the cAMP transmembrane signaling system in the ga3-mutant. cAMP receptor 1 protein, cyclic nucleotide phosphodiesterase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…Gα2 mediates cAMP‐induced activation of guanylyl cyclase and phospholipase C (Okaichi et al ., 1992; Bominaar and Van Haastert, 1994) and by release of Gβγ of adenylyl cyclase (Wu et al ., 1995a). Gα3 null mutants show an as yet uncharacterized defect in cAMP signal production (Brandon and Podgorski, 1997). Gα4 mediates activation of guanylyl cyclase and, via Gβγ, of adenylyl cyclase by folate, a chemoattractant secreted by bacteria (Hadwiger et al ., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Gα2 mediates cAMP‐induced activation of guanylyl cyclase and phospholipase C (Okaichi et al ., 1992; Bominaar and Van Haastert, 1994) and by release of Gβγ of adenylyl cyclase (Wu et al ., 1995a). Gα3 null mutants show an as yet uncharacterized defect in cAMP signal production (Brandon and Podgorski, 1997). Gα4 mediates activation of guanylyl cyclase and, via Gβγ, of adenylyl cyclase by folate, a chemoattractant secreted by bacteria (Hadwiger et al ., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The developmental arrest of amiB À cells possibly resulted in inef®cient synergetic development with wild-type cells. These features distinguish the amiB À mutant from other early developmental mutants such as those of RasG, one member of Ras family proteins, Ga3, a G-protein alpha subunit, and DdMyb2, all of which are essential for early development (Khosla et al 1996;Brandon & Podgorski 1997;Otsuka & Van Haastert 1998). Wild-type cells expressing constitutively active RasG (G12T) as well as ga3 À and Ddmyb2 À cells, fail to express normal levels of cAR1 or ACA and display the aggregate-less phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The strains used in this study are shown in Table 1. Cells were grown in liquid culture and starved as described previously in Brandon & Podgorski (1997). HL5 medium for HPS400 and JH10 was supplemented with 100 µg/mL thymidine.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that a strain of cells containing a targeted disruption of the Dictyostelium Gα3 gene ( gα3 – cells) are blocked in aggregation and the expressions of several early development genes are aberrant (Brandon & Podgorski 1997; Brandon et al . 1997).…”
Section: Introductionmentioning
confidence: 99%